1984
DOI: 10.1111/j.1439-0418.1984.tb03718.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical and chemosensory stimuli involved in host recognition and oviposition of the cherry fruit fly Rhagoletis cerasi L.

Abstract: The aim of this study was to find out to which extent the narrow host spectrum of Rhagoletis cerasi Linné (Trypetidae, Diptera) is due to sensory barriéres or unsuitable texture and composition of nonhost fruits. Preference or partial avoidance of fruit dummies made of thin‐walled wax hemispheres (fig. 6) and impregnated with either host‐ or nonhost‐volatiles by gravid R. cerasi was demonstrated. The volatiles of a fruit species were obtained by passing purified air (3 1/min) for 48 hours over ˜ 1 kg of unripe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…Rhagoletis pomonella was more attracted to light‐coloured spheres when the background was dark green than when it was light green or sky, but it was more attracted to dark‐red spheres against skylight than darker foliage (Owens and Prokopy ). This could also be true for R. cerasi , as luminosity contrast of black fruit dummies on a white surface encouraged more oviposition than fruit dummies that had the same colouration as the background (Levinson and Haisch ). Use of contrast by Diptera is not limited to Rhagoletis flies, as it also occurs in house flies, Musca domestica L. and blackflies ( Simulium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Rhagoletis pomonella was more attracted to light‐coloured spheres when the background was dark green than when it was light green or sky, but it was more attracted to dark‐red spheres against skylight than darker foliage (Owens and Prokopy ). This could also be true for R. cerasi , as luminosity contrast of black fruit dummies on a white surface encouraged more oviposition than fruit dummies that had the same colouration as the background (Levinson and Haisch ). Use of contrast by Diptera is not limited to Rhagoletis flies, as it also occurs in house flies, Musca domestica L. and blackflies ( Simulium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Such an oviposition preference on the basis of colour was reported in several Rhagoletis spp. (Prokopy & Boller, 1971; Levinson & Haisch, 1982), C . capitata (Katsoyannos et al., 1986), and Ceratitis rosa Karsch (Quilici & Rivry, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Such an oviposition preference on the basis of colour was reported in several Rhagoletis spp. (Prokopy & Boller, 1971;Levinson & Haisch, 1982), C. capitata (Katsoyannos et al, 1986), and Ceratitis rosa Karsch (Quilici & Rivry, 1996). The colour orange was also reported as an egg-laying stimulus for the females of B. oleae, and Rhagoletis indifferens Curran (Katsoyannos & Pittara, 1983;Katsoyannos et al, 1985;Messina & Jones, 1990).…”
Section: Factors Affecting Oviposition Preferencementioning
confidence: 96%
“…Repellents or mechanical barriers to prevent oviposition: Oviposition behavior of cherry fruit flies is influenced by host fruit characteristics, such as texture [88], surface structure [83], and chemosensory stimuli [88,173,214]. Altering the surface chemistry of cherry fruits might therefore prevent oviposition.…”
Section: Gaps In Knowledge and Future Research Opportunitiesmentioning
confidence: 99%
“…Altering the surface chemistry of cherry fruits might therefore prevent oviposition. Until now only little research has been done on the reaction of R. cerasi to non-host volatiles [214,215]. In addition, physical properties of the fruit surface could be altered: It was shown that oil treatments prevent oviposition of R. cerasi , because the flies were not able to penetrate the slippery, oily skin with the ovipositor [106].…”
Section: Gaps In Knowledge and Future Research Opportunitiesmentioning
confidence: 99%